Using a Project-Based Instructional Programme for Developing EFL Students' Phonological Awareness and Self-Efficacy - Yusra Mohammed Salman (QALAAI ZANIST SCIENTIFIC JOURNAL, 2025)
Phonological awareness and self-efficacy are crucial skills for EFL students, impacting their comprehension and linguistic performance. However, many EFL students encounter difficulties in these areas, particularly while studying pronunciation and phonology courses. This study explores the impact of project-based learning (PBL) with a focus on multiple intelligences (MI) on the enhancement of phonological awareness and self-efficacy among English as a Foreign Language (EFL) students facing challenges in pronunciation and phonology courses. With a mixed-methods design involving 79 second-year university EFL students, the eight-week PBL programme integrates tasks aligned with students' dominant intelligences and themed around "English around the world." The study reveals significant improvements in both phonological awareness and self-efficacy, underscored by a positive correlation between the scores. Qualitative insights from interviews complement the quantitative findings, highlighting heightened interest, motivation, collaboration, creativity, and autonomy in English learning through PBL and MI. Despite these advantages, the study acknowledges challenges in areas such as time management, group work, and assessment. In conclusion, PBL and MI emerge as effective and engaging pedagogies for EFL students, contributing meaningful insights to the literature and offering practical recommendations for practitioners and researchers to optimize the implementation of these approaches for the development of phonological awareness and self-efficacy in EFL contexts.